Self-efficacy and self-regulated learning strategies as significant predictors of english writing proficiency in Chinese EFL senior high school students - Xiaoli Chen; Jingxia Yan; Wenxiu Guo (PLoS ONE, 2026)
Self-efficacy and self-regulated learning strategies are crucial importance for enhancing the writing proficiency of foreign language learners. This study employed a cross-sectional design to examine the relationships among writing self-efficacy, writing self-regulated learning strategies and writing proficiency in Chinese senior high school students learning English as a foreign language (EFL). A convenience sample of 223 participants completed a writing test and two adapted questionnaires: the Questionnaire of English Writing Self-Efficacy (QEWSE) and the Questionnaire of English Writing SRL Strategies (QEWSRLS). Both instruments were adapted the participants’ actual situation and showed good reliability and validity. Students’ writing proficiency was assessed based on essays scored by two independent raters. Correlation analysis was used to examine the relationships between these constructs and writing performance, and confirmatory factor analysis (CFA) was conducted to establish and validate the measurement models. The results showed significant positive relationships between the constructs, indicating that higher levels of self-efficacy and greater use of SRL strategies are associated with better writing performance. There is robust construct validity for both measurement models: a five-dimensional model of writing self-efficacy (RMSEA = 0.030) and a nine-dimensional model of writing SRL strategies (RMSEA = 0.027). These findings underscore the importance of integrating psychological and strategic factors into pedagogical practices to enhance EFL writing instruction in similar contexts.